Optimization of Transnational Governance by the Mekong River Commission in Meeting Clean and Affordable Energy: The 7TH Sustainable Development Goals in the Mekong River Basin - Nufus, Zakiyatun (International Relations Study Program, The Faculty of Social and Political Sciences, UIN Sunan Ampel Surabaya, 2025)
This study focuses on the optimization of transnational governance in the Mekong River basin by the Mekong River Commission in an effort to meet clean and affordable energy needs in line with sustainable development goals (SDG 7). The increase in hydropower dam projects in the Mekong River basin has led to conflicts between regional energy needs, cross border social impacts, and environmental degradation risk. Thus, academic concerns have arisen because the MRC does not have the legal authority to bind member countries to follow established sustainability principles or standards, thereby calling into question the effectiveness of cross-border governance. This research utilizes descriptive qualitative approach with document analysis covering strategic reports, scientific journals, and MRC policies such as the Basin Development Strategy 2021-2030 and the Sustainable Hydropower Development Strategy was used. The results of the study prove that the MRC acts as a technocratic broker or intermediary in the policy process that prioritizes analysis, scientific data, and technical expertise in developing efficient and rational decisions. The findings show operational coordination, regional consultation mechanisms, real-time data exchange, and noncoercive technocratic standardization. The findings also reveal the MRC’s structural challenges, including the limitations of nonbinding legality and the imbalance of power between countries. Nevertheless, the MRC has been able to optimize adaptive, knowledge-based, and collaborative transnational governance in the Mekong River basin’s sustainable hydropower management.